KERAGAMAN SPESIES RAYAP DI KAMPUS UNIVERSITAS NEGERI SEMARANG GUNUNGPATI SEMARANG - Annisa, Shofi; Hestiningsih, Retno; Hadi, Mochamad (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Termites are cause damage to crops and buildings were made of wood. Data about the types of termites and habit living of termite is required to get prevention and control of termite, efficient and enviromentally friendly. The objective of this research was to know the species of termites on the Campus of State University Semarang Gunungpati Semarang and describes the characteristics of the termites were found. This research is descriptive type, survey methods and cross sectional approach. The population of the research was all termite species around buildings on the Campus of State University Semarang Gunungpati Semarang. A sample of termites was warrior caste which taken from a population of termites. The results were analyzed using univariate analysis method, and is represented in frequency distribution tables, diagrams, maps and narrative. The results of research has found 19 soil tunnels species of Macrotermes gilvus, 3 soil tunnels species of Odontotermes javanicus, 4 soil tunnels species of Coptotermes curvignathus and found 3 mound nest of Macrotermes gilvus, 1 mound nest of Odontotermes javanicus, 1 mound nest of Coptotermes curvignathus, and 1 nest of dry wood termite Cryptotermes cyanocephalus. Vegetation of termites found in mahogany, petai china, teak, guava, manggo, and ketapang. The concluded that on the Campus of State University Semarang Gunungpati Semarang there are 4 species of termites, Macrotermes gilvus, Odontotermes javanicus, Coptotermes curvignathus,Â  and Cryptotermes cyanocephalus.